Historia, política y sociedad en las nuevas docuseries periodísticas de la era Netflix: el caso de la España de la transición a la democracia (Monográficos) - Blanco Pérez, Manuel (2022)
The platforms of the Netflix era have caused a veritable tsunami in the film industry, but also in other contributors such as television and journalism. Regarding the latter, it must be said that it is undeniable that it has now lost its exclusivity as the driving force behind the creation of public opinion, since the virality of the networks has condemned the scientific method of journalism (contrasting sources, research, etc.). On the other hand, faced with the struggle of newspapers for a return to the past that is as useless as it is unfeasible, more and more young journalists are using the screens opened up by the platforms to introduce investigative journalistic and reporting products. In the case of Spain, with a very young democracy that is barely forty years old, the best journalistic works, today, of what the transition to democracy meant in the 1980s, are taking place on the platforms. We will analyse from a transversal (semiotic) perspective some of the three series: the most representative proposals and their links with recent Spanish history. Our main conclusion is that the view of the new audiovisual journalism of the Netflix era on the recent history of Spain is still very reductionist and embryonic, but promising in terms of the multiplication of screens and, therefore, the possibility of disseminating other discourses that have hitherto been minority or quasi-censored.